2021
DOI: 10.1002/bio.4068
|View full text |Cite
|
Sign up to set email alerts
|

Design and strategy for spectrofluorimetric determination of tranexamic acid in its authentic form and pharmaceutical preparations: application to spiked human plasma

Abstract: A creative, very sensitive and noncomplicated spectrofluorimetric technique was established and further validated to determine tranexamic acid in both its authentic form and its pharmaceutical preparation dosage forms. In the introduced technique, a reaction was found between the aliphatic primary amino group of tranexamic acid and ninhydrin/phenylacetaldehyde reagents in the presence of Torell and Steinhagen buffer pH 7.0, which led to the production of a highly fluorescent product; fluorescence intensity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The TRX formulations are available as tablets (Kapron 500 mg) or ampoules (Bledex 500 mg/5 ml) in the Egyptian pharmacy. Both were examined using both the novel method and the previously published technique [21]. The findings of the formulation percentage recovery test were good and closely matched the label's value.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The TRX formulations are available as tablets (Kapron 500 mg) or ampoules (Bledex 500 mg/5 ml) in the Egyptian pharmacy. Both were examined using both the novel method and the previously published technique [21]. The findings of the formulation percentage recovery test were good and closely matched the label's value.…”
Section: Resultsmentioning
confidence: 76%
“…The findings of the formulation percentage recovery test were good and closely matched the label's value. Utilizing precision in the mean of the F ‐test and accuracy in the mean of the t ‐test in comparison to the reported [21] method, the relevance of the method was assessed. The tabulated values in Table 6 were higher than the estimated values, and a 95% confidence level indicated that there was no disagreement with the approach that had been presented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally to assay drugs that have primary amine groups, 2,2-dihydroxyindan-1,3-dione is employed as a derivatizing agent in presence of phenylacetaldehyde. [23][24][25][26] The reagent reacts with the main amino moiety in the structure resulting in a highly yellow uorescent derivative. Precision, repeatability, and lower analytical cost are the main key benets that distinguish this condensation reaction.…”
Section: Resultsmentioning
confidence: 99%